LA LINTERNA MÁGICA EN BARCELONA: LAS FANTASMAGORÍAS DEL ÓPTICO FRANCISCO DALMAU (1844-1848) - Cèlia CUENCA CÓRCOLES, (Fonseca, Journal of Communication, 2023)
This article will present the magic lantern shows that the Catalan optician Francisco Dalmau (1810-1886) celebrated in Barcelona between 1844 and 1848. Being a key figure on the introduction of the telephone and the phonograph in Spain, his interest in optical shows has been obscured by his scientific activities. I will first discuss the presence of the magic lantern in Barcelona at the beginning of the century, to then consider Dalmau’s shows and his interplay with the media landscape of his time. By focusing on Dalmau’s shows, this article also arises a new light on the presence and development of the magic lantern in Barcelona, such as the introduction of the dissolving views.